Securing Regional Influence in a Contested Pacific: The Pukpuk Treaty as Instrument of Australia’s Foreign Policy toward Papua New Guinea - Ferditania Estirahayu; Rodon Pedrason; Anak Agung Banyu Perwita (Darul Yasin Al Sys, 2026)
Although geopolitical competition in the Pacific has attracted increasing scholarly attention, studies specifically examining the Pukpuk Treaty as a multidimensional instrument of Australia’s foreign policy toward Papua New Guinea (PNG) remain limited. Existing scholarship has largely emphasized Australia–China rivalry at the macro-regional level, while the interaction between strategic competition, bureaucratic dynamics, and defense diplomacy within the treaty framework remains underexplored. This study aims to analyze how Australia uses the Pukpuk Treaty to maintain regional influence amid intensifying geopolitical competition in the Pacific. Using a qualitative case study approach, the research examines Australia–PNG security relations within the broader Indo-Pacific strategic environment. Data were collected through document analysis and literature review of official government publications, policy reports, bilateral cooperation documents, and academic literature. The analysis applies Neoclassical Realism, the Bureaucratic Politics Model, and Defense Diplomacy as complementary analytical frameworks. The findings indicate that the Pukpuk Treaty reflects a shift in Australia’s Pacific strategy from development-oriented engagement toward institutionalized security cooperation. The treaty functions not only as a bilateral defense arrangement but also as a mechanism for preserving Australia’s regional leadership, strengthening institutional alignment with PNG, and limiting China’s growing influence. The study concludes that the Pukpuk Treaty plays an important role in shaping regional security architecture and alignment dynamics in the Pacific. This study contributes to foreign policy and Indo-Pacific security studies by clarifying how defense diplomacy, bureaucratic interests, and strategic competition intersect in Australia’s engagement with PNG.